Factorial analysis of slaughter characteristics of fattening pigs fed different additives–Enzyme and probiotic in mixtures - Blazenka Popovic; Branislav Zivkovic; Radojka Maletic; Zoran Rajic; Svjetlana Jankovic-Soja (African Journal of Pig Farming, 2017)
To successfully investigate slaughter characteristics of fattening pigs fed in different ways, this experiment was carried out on Experimental Farm of the Institute for Animal Husbandry, Belgrade-Zemun. Investigation of correlation between slaughter traits of pigs fed with different additives in their nutrition was done by factorial analysis. Slaughter characteristics in three groups of fattening pigs fed in different ways were observed. The first group (variant 1) consisted of fatteners fed diets without any special additives. The second group (variant 2) consisted of pigs fed diets containing enzyme Rovabio, and the third group (variant 3) probiotic Lacture + Microbond. This study was aimed at coming to conclusion based on the results of factorial analysis of the observed traits to the greatest extent which determined slaughter traits of pigs fed diets containing different additives. The results obtained in general, that is, the structure of separated factors showed that different slaughter characteristics are realized with different nutrition.